The development of platinum-based alloys and their thermodynamic database - Cornish L.A.; Hohls J.; Hill P.J.; Prins S.; Süss R.; Compton D.N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A series of quaternary platinum-based alloys have been demonstrated to exhibit the same two-phase structure as Ni-based superalloys and showed good mechanical properties. The properties of ternary alloys were a good indication that the quaternary alloys, with their better microstructure, will be even better. The quaternary alloy composition has been optimised at Pt84:Al11:Ru2:Cr3 for the best microstructure and hardness. Work has begun on establishing a thermodynamic database for Pt-Al-Ru-Cr alloys, and further work will be done to enhance the mechanical and oxidation properties of the alloys by adding small amounts of other elements to the base composition of Pt84:Al11:Ru2:Cr3.